Calculus early transcendentals - Stewart, James 1941- (Belmont, CA Thomson Brooks/Cole, 2008)
"Success in your calculus course starts here! James Stewart's CALCULUS texts are world-wide best-sellers for a reason: they are clear, accurate, and filled with relevant, real-world examples. With CALCULUS: EARLY TRANCENDENTALS, Sixth Edition, Stewart conveys not only the utility of calculus to help you develop technical competence, but also gives you an appreciation for the intrinsic beauty of the subject. His patient examples and built-in learning aids will help you build your mathematical confidence and achieve your goals in the course!"--Amazon.com.
15. Multiple integrals -- 15.1. Double integrals over rectangles -- 15.2. Iterated integrals -- 15.3. Double integrals over general regions -- 15.4. Double integrals in polar coordinates -- 15.5. Applications of double integrals -- 15.6. Triple integrals -- Discovery project : volumes of hyperspheres -- 15.7. Triple integrals in cylindrical coordinates -- Discovery project : the intersection of three cylinders -- 15.8. Triple integrals in spherical coordinates -- Applied project : roller derby -- 15.9. Change of variables in multiple integrals -- Review -- Problems plus -- 16. Vector calculus -- 16.1. Vector fields -- 16.2. Line integrals -- 16.3. The fundamental theorem for line integrals -- 16.4. Green's theorem -- 16.5. Curl and divergence -- 16.6. Parametric surfaces and their areas -- 16.7. Surface integrals -- 16.8. Stokes' theorem -- Writing project : three men and two theorems -- 16.9. The divergence theorem -- 16.10. Summary -- Review -- Problems plus -- 17. Second-order differential equations -- 17.1. Second-order linear equations -- 17.2. Nonhomogeneous linear equations -- 17.3. Applications of second-order differential equations -- 17.4. Series solutions -- Review -- Appendixes -- A. Numbers, inequalities, and absolute values -- B. Coordinate geometry and lines -- C. Graphs of second-degree equations -- D. Trigonometry -- E. Sigma notation -- F. Proofs of theorems -- G. The logarithm defined as an integral -- H. Complex numbers -- I. Answers to odd-numbered exercises.
Metric international version.
Includes index.
Keywords: Calculus -- Textbooks; Transcendental functions -- Textbooks